2022
DOI: 10.1093/bjsopen/zrac122
|View full text |Cite
|
Sign up to set email alerts
|

Routine pathologic evaluation of circular stapler anastomotic rings is not useful after resection for colorectal cancer: retrospective study and systematic review with meta-analysis

Abstract: Background Circular staplers are commonly used for reconstruction after radical resection for colorectal cancer. Pathological analysis of the anastomotic rings is common practice, although the benefits are unclear. The purpose of this study was to evaluate the usefulness of routine histopathological analysis of anastomotic rings in an original series and in a systematic review of the literature. Method The retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In particular, a large Canadian study 3 , analysing circular stapler anastomotic rings specimens from nearly 490 CRC resections, confirmed that their routine pathologic evaluation is not useful, as no patients had cancer in the ring specimen, 5.1 per cent had benign pathological findings and patients’ management was never affected by this result. Also, in another registry study including nearly 6200 patients from Sweden 4 , authors documented that the routine use of rectal washout during anterior resection did not impact the 3-year oncological outcomes, even if a reduction in local recurrence risk after the 5-year follow-up was observed.…”
mentioning
confidence: 99%
“…In particular, a large Canadian study 3 , analysing circular stapler anastomotic rings specimens from nearly 490 CRC resections, confirmed that their routine pathologic evaluation is not useful, as no patients had cancer in the ring specimen, 5.1 per cent had benign pathological findings and patients’ management was never affected by this result. Also, in another registry study including nearly 6200 patients from Sweden 4 , authors documented that the routine use of rectal washout during anterior resection did not impact the 3-year oncological outcomes, even if a reduction in local recurrence risk after the 5-year follow-up was observed.…”
mentioning
confidence: 99%